2023
DOI: 10.1021/acs.jmedchem.2c01799
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Ebselen-Based Inhibitors of Bacterial Ureases with Nontypical Mode of Action

Abstract: Screening of 25 analogs of Ebselen, diversified at the N-aromatic residue, led to the identification of the most potent inhibitors of Sporosarcina pasteurii urease reported to date. The presence of a dihalogenated phenyl ring caused exceptional activity of these 1,2-benzisoselenazol-3(2H)-ones, with Ki value in a low picomolar range (<20 pM). The affinity was attributed to the increased π–π and π–cation interactions of the dihalogenated phenyl ring with αHis323 and αArg339 during the initial step of binding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Two of these small molecule inhibitors (64, 65) have a 4-halopyridine scaffold that function as covalent quiescent affinity labels and two are benzimidazole-like inhibitors that reversibly and competitively inhibit human DDAH1. Ebselen was also identied as a potent hDDAH1 inhibitor from this study, however, this compound binds to multiple targets [37][38][39] therefore complicating its use in the clinical setting. A high number of false positives noted in this study highlights the potential challenges in screening new DDAH1 inhibitors.…”
Section: Irreversible Ddah1 Inhibitorsmentioning
confidence: 99%
“…Two of these small molecule inhibitors (64, 65) have a 4-halopyridine scaffold that function as covalent quiescent affinity labels and two are benzimidazole-like inhibitors that reversibly and competitively inhibit human DDAH1. Ebselen was also identied as a potent hDDAH1 inhibitor from this study, however, this compound binds to multiple targets [37][38][39] therefore complicating its use in the clinical setting. A high number of false positives noted in this study highlights the potential challenges in screening new DDAH1 inhibitors.…”
Section: Irreversible Ddah1 Inhibitorsmentioning
confidence: 99%
“…In addition, urease-negative mutants of P. mirabilis can colonize the urinary tract, and this colonizing capacity is around 100 times lower than that in the parental strain [90]. Ebselen has been found to inactivate H. pylori urease with Ki in the nanomolar range [87], and biological studies on ebselen-derived compounds have shown potent inhibition of ureolysis in whole P. mirabilis cells in a urine model [91].…”
Section: Ebselen's Efect On Virulence Factors Of Gram-negativementioning
confidence: 99%
“…R f = 0.22 (PE/AcOEt 8:2). 1 (36). Following the general method E using chalcone (14), compound 36 was obtained as a white solid in 40% yield.…”
Section: 1 5 N ′ -( ( 1 E 2 E ) -3 -( -C H L O R O P H E N Y L ) ...mentioning
confidence: 99%
“…In particular, thiosemicarbazone and thiazoline derivatives have been an object of considerable interest as potential urease inhibitors in recent years. , Our research group has worked on the search for new urease inhibitors for several years . We have reported the relevance of various scaffolds, and this paper describes our first attempt to characterize thioureas. We exploited the aforementioned scaffolds that, with the exception of the thiazole ring (Figure C), contained thiourea fragments. Because thiazole had been reported for its antiureolytic activity, it was considered a promising scaffold as well and has been additionally modified to serve as a thiourea derivative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation